2002
DOI: 10.1002/eat.10006
|View full text |Cite
|
Sign up to set email alerts
|

The role of acculturative stress and body dissatisfaction in predicting bulimic symptomatology across ethnic groups

Abstract: The combination of acculturative stress and body dissatisfaction may render minority women more vulnerable to bulimic symptoms; the absence of acculturative stress among minority women may buffer them against bulimic symptoms, even in the presence of body dissatisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
98
1
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(110 citation statements)
references
References 54 publications
6
98
1
4
Order By: Relevance
“…Ideally, sample sizes would be large enough to compare ethnic minority groups separately. The current study also did not include a measure of acculturation, which has been shown to be related to eating disorder symptoms among ethnic minorities (Perez, Voelz, Pettit, & Joiner, 2002). If the ethnic minority families in our sample were generally well acculturated, it is possible that ethnicity may not be a distinguishing factor when examining family interaction.…”
Section: Discussionmentioning
confidence: 94%
“…Ideally, sample sizes would be large enough to compare ethnic minority groups separately. The current study also did not include a measure of acculturation, which has been shown to be related to eating disorder symptoms among ethnic minorities (Perez, Voelz, Pettit, & Joiner, 2002). If the ethnic minority families in our sample were generally well acculturated, it is possible that ethnicity may not be a distinguishing factor when examining family interaction.…”
Section: Discussionmentioning
confidence: 94%
“…Reasons why Blacks are experiencing a higher prevalence in BN have been postulated to be associated with stress, including acculturated stress. 12 That is, the more Blacks feel pressure to assimilate with the dominant culture in America, the greater their risk for body image dissatisfaction and development of BN. 12 Perhaps the positive body self perceptions that once protected Blacks from eating disorders may be beginning to erode.…”
Section: Resultsmentioning
confidence: 99%
“…12 That is, the more Blacks feel pressure to assimilate with the dominant culture in America, the greater their risk for body image dissatisfaction and development of BN. 12 Perhaps the positive body self perceptions that once protected Blacks from eating disorders may be beginning to erode. 13 Consistent with previous research, 2,9 binge eating was the most prevalent eating disorder among Blacks in the NSAL.…”
Section: Resultsmentioning
confidence: 99%
“…Scores range from 21 to 105, with higher scores indicating higher levels of acculturative stress. Studies have found the internal consistency estimate to range from .87 to .89 with African American participants (Perez et al 2002;Joiner and Walker 2002). Coefficient alpha for this study was .92.…”
Section: Acculturative Stressmentioning
confidence: 88%